Generating Electricity Using Photovoltaic Solar Plants in Iraq - Chaichan, Miqdam Tariq (Springer International Publishing, 2018)
This book focuses on solar energy and its applications in Iraq and its neighboring countries. Iraq suffers from electricity shortages and faces many challenges to meet and overcome current and future increases in electrical demand. Although Iraq relies primarily on petroleum as an energy source, many scientists agree that the future of energy efficiency and safety will rely heavily on the implementation of green and renewable energies. This book is aimed at researchers, policymakers, and students and discusses how PV systems can be successfully implemented in order to reduce dependency on fossil fuel resources. Contains case studies and examples to enhance practical application of the technologies presented; Presents actual adopted Iraqi PV projects; Explains the use and application of photovoltaic cells.